2010
DOI: 10.1097/jcp.0b013e3181fbfac4
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the 1291-C/G Polymorphism in the Adrenergic α-2a Receptor and the Metabolic Syndrome

Abstract: The prevalence of the metabolic syndrome is increased in patients with schizophrenia compared with the general population. The strong interindividual differences in susceptibility to developing the metabolic syndrome suggests that the genetic makeup is a modulating factor. Part of the genetic puzzle can possibly be explained by variations in the gene coding for the adrenergic α-2a receptor (ADRA2A) because this receptor plays an important role in lipolysis. Three studies have found an association between the α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Arg347 allele in Alpha-1A adrenergic receptor (ADRA1A)[123] has been demonstrated to be associated with a high prevalence and alpha-2A adrenergic receptor (ADRA2A) 1291-G allele with lower prevalence of MetS. [124] Similarly COMT158Val allele was shown to be associated with MetS prevalence in one of the studies. [30] Kang et al .…”
Section: Predictors Of Mets In Schizophreniamentioning
confidence: 99%
“…Arg347 allele in Alpha-1A adrenergic receptor (ADRA1A)[123] has been demonstrated to be associated with a high prevalence and alpha-2A adrenergic receptor (ADRA2A) 1291-G allele with lower prevalence of MetS. [124] Similarly COMT158Val allele was shown to be associated with MetS prevalence in one of the studies. [30] Kang et al .…”
Section: Predictors Of Mets In Schizophreniamentioning
confidence: 99%
“…One study reported an association with the leptin promoter SNP, but not with the -759C/T HTR2C SNP;46) however an interaction between the two polymorphisms was observed. Another group did find, and replicated, association of metabolic syndrome with another HTR2C SNP47) and with the α2A adrenoceptor gene 48)…”
Section: Pharmacogenetic Findingsmentioning
confidence: 89%
“…No significant association was found for ADRA2A. 152 Polymorphisms in the apolipoprotein A-V (APOA5) and C-III (APOC3) genes, but not in LEP, showed an influence on triglyceride and cholesterol levels in patients treated with clozapine or olanzapine. 74 Agranulocytosis is a serious adverse effect associated with clozapine.…”
Section: Studies Assessing the Adverse Effects Of Clozapinementioning
confidence: 90%